Pendampingan Sosialisasi Cemaran Khamr dan Alkohol Dalam Makanan Sebagai Persiapan Menghadapi Sertifikasi Halal - Sari, Dewi Hambar; Tanfidiyah, Nur (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
One of the food-product halalness indicator is the absence of alcohol. In this case, traders as business actors must know about the contamination of khamr and alcohol in food ingredients that are traded so as not to endanger themselves and consumersas a condition when applying for halal certification. Because the content of khamr and alcohol besides endangering health, the Qur'an also clearly forbids them.Therefore this community service aims to increase the knowledge of shop owners around IAIN Surakarta regarding the contamination of khamr and alcohol in food as an effort to prepare for halal certification. This activity is carried out using the socialization method, namely by giving lectures and questions and answers to 10 food stall owners. Activity evaluation is carried out by providing a pre-test and post-test on the topic presented. From this community service activity, there was an increase in knowledge which could be seen from the pre-test and post-test scores, which were respectively 36 and 86. Specifically, the increase in knowledge about the definition of alcohol and khamr was 50%, the rules of the beverage trade. alcohol in Indonesia is 50%, types of alcoholic drinks are 60%, and the law of alcohol and khamr in Islam is 30%.